Art of Maternal Womb Painting: term, concept, and technique - Júnia Aparecida Laia da Mata; Antonieta Keiko Kakuda Shimo
ABSTRACT Objective: to present the term, concept and technique of art of maternal womb painting. Method: a theoretical, exploratory and qualitative study. Results: from the results, the concept was elaborated and based on linguistic, philosophical and specialized perspective. The concept and technique of Art of Maternal Womb Painting were guided by humanism and holism. Final considerations: this study can broaden the visibility of this visual art and insert it in the obstetrics, as well as its adoption by nurses, midwives and other health professionals in humanistic and holistic care for maternal health.